Upaya Meningkatkan Hasil Belajar Matematika dengan Menggunakan Model Explicit Instruction dan Course Review Horay Berbantu Media Manipulatif pada Peserta Didik Kelas V B di SDN-3 Langkai Palangkaraya Tahun Pelajaran 2017/2018: Efforts to Improve Learning Outcomes of Mathematics Using Manipulative Media Explicit Instruction and Course Review Horay Models in Class V B Students in Langkai Palangkaraya SDN-3 2017/2018 Academic Year - Desi Dwi Mariana Putri; Ichyatul Afrom (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to describe the learning activities of Mathematics by using the Explicit Instruction Model and Course Review Horay model assisted by manipulative media and improving Mathematics learning outcomes using the Explicit Instruction model and Course Review Horay with the help of the manipulative press. This type of research is classroom action research (CAR). The subjects of this study were 27 students of class V B, consisting of 15 men and 12 women. Data collection techniques in this study used tests and observations. Data analysis used qualitative and quantitative analysis. The results showed that the learning activities of students using the Explicit Instruction and Course Review Horay models assisted manipulative media in students increased, the average value of the first cycle was 2.87 with poor criteria and the second cycle the average cost was 3.32 with suitable measures. Also, there is an increase in Mathematics learning outcomes using the Explicit Instruction model and the Course Review Horay assisted by manipulative media in class students. The average pre-test value is 44 with classical completeness of 25%, the cycle I average cost 63 with artistic integrity 51.85%, and in cycle II the average cost is 79 with artistic integrity 92.59%